Trends in adolescent pertussis burden: a systematic analysis from 1990 to 2021 in global, regional, and national within the global burden of disease study 2021, with forecasts for 2046 - Zhu, Huihui; Lv, Fangfang; Wen, Shunhang; Xu, Ming; Zhang, Hailin (Frontiers in Pediatrics, 2025)
BackgroundPertussis, a highly contagious respiratory disease caused by Bordetella pertussis, traditionally associated with children, is now increasingly transmitted by adolescents (ages 10–19) and adults. Using data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2021 (GBD 2021), we estimated the disease burden of pertussis among adolescents.MethodsWe analyzed adolescent pertussis data from GBD 2021, assessing prevalence, incidence, mortality, and Disability-Adjusted Life Year (DALY) rate across global, regional, and national levels. Temporal trends were quantified with the Estimated Annual Percentage Change (EAPC), and decomposition and prediction models were employed for further insights.ResultsFrom 1990 to 2021, adolescent pertussis prevalence, incidence, mortality, and DALY rate declined markedly worldwide. Declines were most pronounced in High and High-middle Socio-Demographic Index (SDI) regions, whereas Low SDI regions maintained the highest burden in 2021. Across the 21 GBD regions, the prevalence, incidence, mortality, and DALY rates have all declined. However, in Central Sub-Saharan Africa, the number of prevalence cases, incidence cases, deaths, and DALYs have increased, while these values have significantly decreased among adolescents in the other 20 GBD regions. Nationally and territorially, the study found substantial variability in the burden of pertussis among adolescents. Decomposition analysis indicated that epidemiological changes primarily drove the decline in most regions, though population growth contributed to increases in some areas. Projection models suggest that the global adolescent pertussis burden will reach its peak in 2022, followed by a gradual decline through 2046.ConclusionsDespite an overall global decline, pertussis remains a public health concern among adolescents due to their role in disease transmission. Strengthening epidemiological understanding in this age group is essential for effective prevention and control strategies.